2020
DOI: 10.1002/term.3118
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin hydrogels promote scar formation and prevent therapeutic angiogenesis in the heart

Abstract: Therapeutic angiogenesis is the delivery of factors to promote vascular growth and holds promise for the treatment of ischemic heart conditions. Recombinant protein delivery to the myocardium by factor-decorated fibrin matrices is an attractive approach, thanks to the ability to precisely control both dose and duration of the treatment, the use of a clinically approved material like fibrin, and the avoidance of genetic modification. Here, we investigated the feasibility of inducing therapeutic angiogenesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The experimental results showed that fibrotic scars would be formed regardless of how the drug was administered; that is, the formation of scars was directly induced by fibrin and was unrelated to the delivery of growth factors, suggesting that the underlying molecular mechanisms must be further studied to prevent serious side effects. [ 151 ]…”
Section: Injectable Hydrogel‐based Therapy For Hfmentioning
confidence: 99%
“…The experimental results showed that fibrotic scars would be formed regardless of how the drug was administered; that is, the formation of scars was directly induced by fibrin and was unrelated to the delivery of growth factors, suggesting that the underlying molecular mechanisms must be further studied to prevent serious side effects. [ 151 ]…”
Section: Injectable Hydrogel‐based Therapy For Hfmentioning
confidence: 99%
“…66,67 Although the use of fibrin could be promising in all tissue regeneration strategies, it could have side effects; for example, in the treatment of cardiac or skin tissue lesions, it might produce undesirable fibrous scars. 68,69 Fibrous scars are characterized by the excessive deposition of extracellular matrix components, particularly collagen, which leads to impaired tissue function and limited regenerative potential. The formation of fibrous scars during fibrin-based tissue regeneration can be attributed to several factors.…”
Section: Fibrin Hydrogel Degradationmentioning
confidence: 99%
“…Rather, the presence of fibrin per se was enough to start the myocardial scarring process. Interestingly, despite the fact that fibrin hydrogels were completely degraded within 5 days, the resulting scars persisted at least 4 weeks without any sign of resolution, suggesting that, once started, the process is irreversible (Melly et al 2020). Interestingly, a recent report by the group of Serena Zacchigna shows that treatment with a monoclonal antibody blocking a specific BMP1 isoform (BMP1.3) can reduce cardiac fibrosis and scar formation in models of myocardial infarction, in part through downregulation of TGF-β signaling and myofibroblast activation (Vukicevic et al 2022).…”
Section: Fibrinogen-induced Fibrosis -All Is Not So Quiet On the Fibr...mentioning
confidence: 99%
“…Fibrin-induced fibrosis does not appear to be a phenomenon unique to the CNS. In fact, we recently found that fibrin hydrogels promote scar formation in the myocardium, while at the same time jeopardizing the therapeutic effect of angiogenic factor delivery (Melly et al 2020 ). Fibrosis was not due to the presence of growth factors, tissue damage from the injection, the mechanical stiffness of the hydrogel or its volume, nor to an immune reaction.…”
Section: Fibrinogen-induced Fibrosis — All Is Not So Quiet On the Fib...mentioning
confidence: 99%